Srbske in hrvaške ali srbskohrvaške ljudske pesmi Bele Krajine? - Terseglav, Marko (Traditiones (Ljubljana), 2000)
The author analyzes the language of Croatian and Serbian folk songs which have been presented ba the Serbian minority, and also by some Slovenes, in Bela krajina. He maintains that these songs do not contain characteristics of purely Croatian or Serbian languages, but that the language of these songs would be best termed Serbo-Croatian. This hypothesis is based on numerous songs examples in which the Croatian and the Serbian languages from different dialectical areas are mixed
Keywords: hrvaške ljudske pesmi; srbske ljudske pesmi; Ethnopoetics; ljudske pesmi